Trends and patterns of land use change and international aid in sub-Saharan Africa - Ephraim Nkonya; Jawoo Koo; Edward Kato; Zhe Guo (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2013)
The sub-Saharan Africa region recorded the fastest conversion of forest land to agriculture in the past 20 years. The region also has the widest yield gap and together with Latin America and Caribbean has the largest unused arable land. However, there are wide variations across countries and this offers valuable lessons on the drivers of agricultural intensification and land use dynamics. This study shows only few countries experienced a decrease in cropland extent. Additionally, few countries with low agricultural potential have shown higher actual maize yield while others with high potential have shown lower actual yield.
Keywords: F18; Q15; Q16; Q18; 330; croplands; aid; agricultural intensification; markets; land rights; governance